A Study on the Ectoparasites and Hemoparasites Infections in Rodents from the Kilwa district, Tanzania - Pilato Waya; Martin Martin; Christopher Sabuni (Universitas Airlangga, 2025)
Background: Ectoparasites play a significant role in facilitating the transmission of disease pathogens and parasites that affect animals and humans. Purpose: This study aims to assess the prevalence of ectoparasites and hemoparasites in rodents from the Kilwa district, Tanzania. Method: A cross-sectional study was conducted to trap 138 rodents using Sherman and wire cage traps. Ectoparasites were removed from rodents by using fine brushes and identified based on morphological features using a Stereo microscope with the assistance of dichotomous taxonomic keys. Blood samples were collected from supraorbital veins in captured rodents, and thick and thin smears were made, stained and examined using a Compound Microscope for screening hemoparasite. Results: The overall prevalence of ectoparasites in rodents was 57.87 % with a high infestation of rodents by Echinolaelaps (Laelaps) echidninus (44.20%) than Laelaps nuttalli (10.87%), Xenopsylla cheopis (12.32%), and Rhipicephalus appendiculatus (2.90%). Most ectoparasites were found in M. natalensis 76.40% followed by R. rattus 25.81%, and G. leucogaster 36.36%. Adult rodents recorded 63.41% of ectoparasites prevalence higher than juveniles 13.33% (p< 0.05). The overall prevalence of hemoparasites in rodents was 18.12%. The identified hemoparasites were Anaplasma sp. (13.04%), Babesia sp. (3.62%), and Trypanosoma sp. (1.45%) observed only in adult rodents. Conclusion: The study recommends engaging and encouraging the community to use integrated pest management practices for rodents and ectoparasite control and prevention to safeguard both human and animal health.